Penjatuhan Hukuman Pidana Mati Terhadap Pelaku Tindak Pidana Narkotika - Muhammad Ilham; Oci Senjaya (Jurnal Ilmiah Wahana Pendidikan, 2022)
Drugs (narcotics, alcohol, psychotropics, and addictive substances) must be used according to legal standards set by the state. Drugs can be used lawfu potentially logical treatment or event. Rapid advances in communication, correspondence, and broadcasting innovation have given rise to a variety of local freedoms and difficulties. Addiction to substances will have an impact on inhibiting the work system of the human body until it causes death. In addition, the use of needles repeatedly can cause HIV/AIDS. The eradication of drug crimes is included in Law no. 35 of 2009 concerning Narcotics with the heaviest criminal sanction being sentenced to death. This research uses a normative juridical approach. Normative jurisprudence is the study of the legal basis, legal system, level of legal agreement, and comparative law. This normative juridical is an attempt to take an inventory of positive law. In this approach, prescriptive rules are used to explore legal issues of compliance with social life.